2014
DOI: 10.3109/00952990.2014.945590
|View full text |Cite
|
Sign up to set email alerts
|

Impact of acute guanfacine administration on stress and cue reactivity in cocaine-dependent individuals

Abstract: Background Stress and drug-paired cues increase drug craving and noradrenergic activity in cocaine-dependent individuals, thus medications that attenuate noradrenergic activity may be effective therapeutic treatment options for cocaine-dependent individuals. Objectives To examine the impact of acute administration of the α-2 adrenergic receptor agonist guanfacine on responses to multiple risk factors for relapse in cocaine-dependent individuals. Methods In a double-blind, placebo-controlled study, cocaine-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Several studies have reported that during human abstinence from drug use, stress exposure often occurs in the presence of contextual cues that had previously been associated with drug use (Epstein et al, 2009); these cues alone may cause a renewal of responding after abstinence. In addition, in a similar manner to the drug cue-induced reinstatement mentioned above, human studies have indicated that stressor exposure can lead to cue-induced drug craving (Mantsch et al, 2015;Moran-Santa Maria et al, 2015;Fox et al, 2014). Furthermore, Sinha et al (1999) and Sinha (2001) reported a clinical trial based on the rodent stressinduced reinstatement paradigm.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Several studies have reported that during human abstinence from drug use, stress exposure often occurs in the presence of contextual cues that had previously been associated with drug use (Epstein et al, 2009); these cues alone may cause a renewal of responding after abstinence. In addition, in a similar manner to the drug cue-induced reinstatement mentioned above, human studies have indicated that stressor exposure can lead to cue-induced drug craving (Mantsch et al, 2015;Moran-Santa Maria et al, 2015;Fox et al, 2014). Furthermore, Sinha et al (1999) and Sinha (2001) reported a clinical trial based on the rodent stressinduced reinstatement paradigm.…”
Section: Discussionmentioning
confidence: 85%
“…In addition, researchers provided a systemic CRH injection to induce physiological (ie, increased cortisol release) and psychological (ie, increased anxiety) stress responses. Since then, many researchers have examined the effects of different drugs on stressinduced relapse (Moran-Santa Maria et al, 2015;Sinha et al, 2007;Fox et al, 2012;McKee et al, 2014), but none have observed the potential effect of PACAP on stress-induced relapse. PACAP treatments may locally target BNST PAC1/ VPAC2 receptors via systemic injection in an effort to antagonize receptors and prevent PACAP binding that facilitates stress responses and, subsequently, stress-induced relapse to drug seeking.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the human studies with alpha-2 adrenoceptor agonists and prazosin appear to support the translational utility of the stress-induced reinstatement model. However, unlike the uniform effects of these agonists on stress-induced reinstatement in the rat model, the effects in the human studies are more variable, and some of the human studies reported negative results (Krupitsky et al, 2013;Moran-Santa Maria et al, 2015a), possibly due to the use of doses that were lower than those used in the studies that report positive effects. The human studies also suggest potential sex differences in the efficacy of alpha-2 adrenoceptor agonists (Fox et al, 2014), a factor that has not been considered in the preclinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, another preliminary study using the imagery task found promising results of α 1 antagonist reducing stress-induced craving in alcoholics (i.e., prazosin; Fox et al, 2012a). However, the predicted effects have not been consistent for all subjective (e.g., craving, anxiety) or physiological (e.g., cortisol, blood pressure) measures or task conditions (e.g., stress-vs. drug cue-induced imagery) across all studies (Fox et al, 2012b(Fox et al, , 2014Moran-Santa Maria et al, 2015). Clearly these studies warrant cautious interpretation given the small sample sizes, lack of robust converging evidence across tasks/measures, and previously acknowledged weak evidence of the predictive validity of these surrogate endpoints.…”
Section: Experimental Therapeutics For Addiction: Stress Mechanisms Tmentioning
confidence: 96%